REPRODUCTION AND RECONSTRUCTION OF CULTURE IN THE CONTEXT OF ISLAMIC COMMUNICATION - Murtazza, Iqbal (JURNAL SAHID DA’WATII, 2025)
Culture is a very fundamental thing in an effort to build the personality of a person or a community. Culture is not only understood as a heritage passed down from generation to generation, but also as a result of dynamic interactions between individuals and groups in social, political, and economic contexts. In the current era of globalization, communication has a very important role in shaping the cultural identity of a society. Islamic communication is one of the effective means to reproduce and reconstruct culture. Reproduction and cultural reconstruction are two important concepts that are interconnected in understanding social dynamics and communication. In the context of Islam, these two concepts play an important role in the spread of the teachings, values, and norms that shape muslim society. The purpose of this journal is to explore how cultural reproduction and reconstruction occur in Islamic communication, as well as its implications for social identity, values, and practices. The approach used in this study is a phenomenological qualitative research method, which is to describe and describe the problem being studied according to actual events. Data collection using library research methods. Discussion Results In the form of cultural reproduction, it refers to the ways in which a group or society transfers knowledge, values, beliefs, and practices that are considered important for its survival and identity. Meanwhile, cultural reconstruction involves efforts to maintain the identity of a group or society in the midst of change. With the existence of this journal, it is hoped that it can add insight, provide accurate information, and can be used as study material for da’wah activists and the community and the academic community. Keywords: Reproduksi ; Rekonstruksi ; Budaya ; Komunikasi ; Islam.